(untitled) (Research, Society and Development, 2021)
Propolis is a material collected from plants by bees, used to promote an aseptic environment in the hive, embalming invaders and repairing cracks. It has several recognized biological activities, both in popular and scientific circles: antioxidant, antimicrobial, healing, anesthetic, anti-inflammatory, among others. There are several types of propolis, depending on environmental factors (type of vegetation visited by insects, climate, season) and factors related to the bees themselves. Its chemical composition is very extensive, the most important group being that of flavonoids. This work aimed to carry out a bibliographic review to investigate the anti-inflammatory activity attributed to propolis for centuries. The search for articles and theses in Portuguese, English and Spanish, published in the last 10 years, was carried out in the following databases: SciELO, Google Scholar, PubMed, MEDLINE, CAPES Catalog of Dissertations and Theses, BVS, CRD, Embase, Science Direct, Scopus and Cochrane Library. The articles obtained at the end of the research brought several experiments, in vivo and in vitro, using propolis of the most diverse types, collected in different regions and countries. The results were very favorable in relation to the propolis extracts, which managed to reach potential values in anti-inflammatory tests, especially when compared with isolated substances already recognized as good anti-inflammatory. Still, many studies have brought information about the possible molecular mechanisms of propolis, such as inhibition of production of inflammatory mediators and specific enzymes.